2012
DOI: 10.1186/1742-2094-9-27
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective function for ramified microglia in hippocampal excitotoxicity

Abstract: BackgroundMost of the known functions of microglia, including neurotoxic and neuroprotective properties, are attributed to morphologically-activated microglia. Resting, ramified microglia are suggested to primarily monitor their environment including synapses. Here, we show an active protective role of ramified microglia in excitotoxicity-induced neurodegeneration.MethodsMouse organotypic hippocampal slice cultures were treated with N-methyl-D-aspartic acid (NMDA) to induce excitotoxic neuronal cell death. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
223
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(245 citation statements)
references
References 69 publications
15
223
0
7
Order By: Relevance
“…2 C and D). These experiments demonstrate that slice cultures are a reliable model for effective tissue exposure and induction of diverse reactive microglial phenotypes (33,34).…”
Section: Lps or Ifn-γ Alone Induces Reactive Phenotypes In Microglia mentioning
confidence: 73%
See 1 more Smart Citation
“…2 C and D). These experiments demonstrate that slice cultures are a reliable model for effective tissue exposure and induction of diverse reactive microglial phenotypes (33,34).…”
Section: Lps or Ifn-γ Alone Induces Reactive Phenotypes In Microglia mentioning
confidence: 73%
“…The morphology of dendrites (MAP2 staining) and GABAergic interneurons (parvalbumin staining) that are exquisitely susceptible to metabolic and oxidative stress (27) was well preserved. As a positive control, slice cultures were exposed to glutamate receptor agonists N-methyl-D-aspartate (NMDA; 5 μM) and kainic acid (KA; 5 μM) to induce excitotoxicity (32,33). NMDA+KA resulted in massive neuronal death ( Fig.…”
Section: Lps or Ifn-γ Alone Induces Reactive Phenotypes In Microglia mentioning
confidence: 99%
“…A report by Kim et al [60] showed reduced neurogenesis with minocycline treatment. The depletion and replenishment of microglia were respectively augmented and reduced by N-methyl-D-aspartate-or oxygen glucose deprivation-induced neuronal cell death [61,62]. Faustino et al [63] also reported that microglia depletion enhances inflammation and injury in acute neonatal focal stroke.…”
Section: Microgliamentioning
confidence: 99%
“…It has long been thought that ramified microglia were “resting” in the healthy brain, however, evidence suggests that microglial cells are highly active in their presumed resting state, continually screening their microenvironment with extremely motile processes and protrusions (Nimmerjahn, Kirchhoff, & Helmchen, 2005). Moreover, it has been shown that ramified microglia not only monitor their microenvironment but also protect hippocampal neurons under pathological conditions (Vinet et al., 2012). Thus, according to the present experimental conditions, these observations suggest that hippocampal organotypic slices present active and neuroprotective ramified microglia.…”
Section: Discussionmentioning
confidence: 99%